Interprofessionele kliënt-gefokusde samewerking in die sekondêre skool tussen die opvoedkundige sielkundige en die onderwyser - Smit, Sarina (2014)
M.Ed. (Educational Psychology) === The pressure exerted on schools in South Africa to provide student support is ever increasing. This is directly attributable to the lack of support in the child’s home, often with both parents being absent due to work obligations. As a result, the growing need for classroom support rests solely upon the teacher. Teachers are finding themselves in a very difficult position, firstly to find the time with already full schedules looking after the curriculum and extramural activities, and secondly feeling incompetent to adequately provide the learner with the required support. The need for inter-professional collaboration between the teacher and the educational psychologist is clear. The educational psychologist is adequately trained to provide the necessary learner support, albeit facing a logistical problem of reaching all the learners in the school. To overcome this problem, the help of the teacher is vitally important. The question that arises and which is investigated further in this study, is: What is the nature of this inter-professional collaboration between the teacher and educational psychologist that is required to address the learner’s need for classroom support? To fully grasp and understand this concept of collaboration, the analysis has been applied within the framework of the existing interaction model which classifies it into two dimensions, one being relationship interaction and the other the interaction with the organisational milieu. The research methodology used in this study can be described as a qualitative study. The study took place within an interpretative paradigm with participants being chosen using a goal-orientated sample. The participants were selected from a single school within the Gauteng educational system, to ensure the study remains focused. The data were collected from research journals, semi-structured individual interviews and uncompleted questionnaires. Finally, the data was analysed by making use of a qualitative content analysis method.